2015
DOI: 10.2298/hemind131128050i
|View full text |Cite
|
Sign up to set email alerts
|

The improved photostability of naproxen in the inclusion complex with 2-hydroxypropyl-β-cyclodextrin

Abstract: The aim of this work was the preparation of the inclusion complex of naproxen with 2hydroxypropyl-β-cyclodextrin (HP-β-CD) in order to improve the physical and chemical properties of naproxen. The molecular inclusion complexes of naproxen with HP-β-CD were prepared by using the co-precipitation method in the solid state with the molar ratio of 1:1. The structure of the obtained complex was characterized by using FTIR, 1 H NMR, UV-Vis and XRD methods. The testing of naproxen photostability by the UV-Vis method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
3
14
0
1
Order By: Relevance
“…Finally, TBPs 1, 2, 13 and 14 are detected only in samples after 240 min of treatment and at low concentration levels and thus they can be considered as later stage products. For the sake of comparison with other studies dealing with the degradation of PRX, TBP 14 and structurally similar TBPs have been identified as degradation products of PRX under oxidative and photolytic conditions . In addition, the in vivo formation of the metabolic oxidation product 5‐hydroxypiroxicam and at least 13 new secondary peaks (without structure identification) after the in vitro study of hydroxyl radical attack of PRX was reported elsewhere …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Finally, TBPs 1, 2, 13 and 14 are detected only in samples after 240 min of treatment and at low concentration levels and thus they can be considered as later stage products. For the sake of comparison with other studies dealing with the degradation of PRX, TBP 14 and structurally similar TBPs have been identified as degradation products of PRX under oxidative and photolytic conditions . In addition, the in vivo formation of the metabolic oxidation product 5‐hydroxypiroxicam and at least 13 new secondary peaks (without structure identification) after the in vitro study of hydroxyl radical attack of PRX was reported elsewhere …”
Section: Resultsmentioning
confidence: 94%
“…Ring cleavage of this unstable intermediate, leads to its conversion in a carboxylic acid structure, as depicted in Fig. which is further transformed to later stages TBPs, such as TBP 1, 2, 13 and 14. The same degradation mechanism was proposed for the photochemical oxidation of PRX …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tworzenie kompleksów inkluzyjnych z cyklodekstrynami jest coraz częściej badane i chętniej wykorzystywane. Dzięki oddziaływaniom z API połączenie takie zwiększa rozpuszczalność substancji (ibuprofen [23]), zwiększa jej stabilność (modafinil [24]), fotostabilność (naproksen [25]) i biodostępność (indometacyna [26]), redukuje działanie drażniące (itrakonazol [27]) i liczbę działań niepożądanych, maskuje nieprzyjemny zapach i smak (famotydyna [28]). Z drugiej jednak strony może się zdarzyć, że zainkludowanie substancji leczniczej do wnętrza cyklodekstryny będzie miało zarówno pozytywne, jak i negatywne efekty.…”
Section: Rycina 2 Budowa β-Cyklodekstrynyunclassified